The interface between adaptive and innate neutralisation of virus entry: competition, addition or synergy? - Wartnaby, Sophie R. (2023)
A complex interplay exists between the innate and adaptive immune systems when responding to viral infections. In particular, complement activity is required to both directly and indirectly eradicate virus infection. The aim of this study was to identify the effect of complement on antibody-mediated virus neutralisation, using Hepatitis C Virus (HCV) as a model. Hepatitis C Virus causes 1.5 million new infections globally every year, with the majority of cases progressing to chronic disease. There is often an asymptomatic acute phase of infection, meaning that early infections are not diagnosed. Complement haemolytic screening (CH50) assay of the classical pathway highlighted there was a significant impairment of complement activity in 75% of chronically infected HCV sera. We confirmed this depletion in complement activity was a genuine result and not due to storage conditions of the sera. The effect of complement on the neutralisation potential of human monoclonal (mAbs) and polyclonal antibodies (HCV-infected IgG), was assessed using an infection model utilising HCV pseudoparticles and human hepatoma cells. It was discovered that mAbs and polyclonal anti-HCV IgG preparations had increased neutralisation potential in the presence of complement, indicating an additional mechanism for the complement cascade in limiting virus infection. This is important for developing immunisation strategies to prevent the spread of HCV and limiting chronic infection. Using this assay, we developed a complement activity depletion model which illustrates the possible outcomes upon HCV infection. This informative model is crucial to understanding how complement function reduces the repercussions of HCV infection and whether complement replacement therapy is necessary alongside DAAs.